Role of oxygen additive on hydrogen impurity incorporation in nanocrystalline diamond films fabricated by microwave plasma chemical vapor deposition - Tang, C. G. (2009)
In this work, we study the influence of oxygen additive in the gas phase on hydrogen impurity incorporation into thick nanocrystalline diamond (NCD) films. Various diamond samples were grown on large silicon wafers of 5.08 cm diameter by adjusting the amount of oxygen and nitrogen additives into a conventional CH4/H2 plasma while keeping the other parameters constant using a 5-kW microwave plasmaassisted chemical vapor deposition (MPCVD) reactor. The morphology, crystalline quality, and hydrogen impurity content of the produced diamond samples were characterized using scanning electron microscopy, micro-Raman spectroscopy, and Fourier transform infrared (FTIR) spectroscopy, respectively. The Raman and the FTIR spectra of the diamond samples indicate that on increasing the amount of oxygen additive in the gas phase, the crystalline quality of the NCD films is significantly enhanced, while their bonded hydrogen content decreases drastically. We conclude that a small amount of oxygen addition has an enhancement effect on the overall quality of diamond films ranging from polycrystalline to nanocrystalline in two ways: improving the diamond crystalline quality and suppressing hydrogen impurity incorporation.